2019
DOI: 10.1089/neu.2018.5700
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Concussive and Subconcussive Injury in a Human Tau Mouse Model Results in Chronic Cognitive Dysfunction and Disruption of White Matter Tracts, But Not Tau Pathology

Abstract: Due to the unmet need for a means to study chronic traumatic encephalopathy (CTE) in vivo, there have been numerous efforts to develop an animal model of this progressive tauopathy. However, there is currently no consensus in the field on an injury model that consistently reproduces the neuropathological and behavioral features of CTE. We have implemented a repetitive Closed-Head Impact Model of Engineered Rotational Acceleration (CHIMERA) injury paradigm in human transgenic (hTau) mice. Animals were subjected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 58 publications
0
21
1
Order By: Relevance
“…[5][6][7][8] Also, data from military and sports-related TBI suggest that this risk is increased when multiple mTBIs are sustained. [9][10][11][12][13][14] Thus, biomarkers that can objectively measure severity of brain injury and predict prognosis of patients with TBI have become an important research focus.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Also, data from military and sports-related TBI suggest that this risk is increased when multiple mTBIs are sustained. [9][10][11][12][13][14] Thus, biomarkers that can objectively measure severity of brain injury and predict prognosis of patients with TBI have become an important research focus.…”
Section: Introductionmentioning
confidence: 99%
“…These studies sought to explore the TBI-CTE link with adult 4–18 months old mice [ 18 , 23 , 24 ], using diffuse closed head injury and focal contusion models of TBI [ 18 , 24 ]. Recent longitudinal studies using adult transgenic mice expressing human tau and rCHI models showed evidence of white matter disease and cognitive and motor dysfunction up to one-year post-injury, without showing a difference in p-tau deposition between sham and injured mice [ 25 ]. Despite the prevalence of adolescent concussions and the recently reported risk of CTE in this population, the impact of rCHI on the progression of tau pathobiology in adolescent mice has not been fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…There are a small number of rCBI studies in mice that have extended observations to a year or longer following injuries and continue to report functional and neuropathological effects of rCBI (1720). These studies, however, have been limited to male mice.…”
Section: Introductionmentioning
confidence: 99%